Impact of feeding strategies on the growth and nutrient discharge in the polyculture of carps using farm ponds - Sharma, Pawan Kumar; Sampath Kumar, John Stephen; MANIKANDAVELU , D (The Indian Journal of Animal Sciences, 2022)
The present study aimed at evaluating appropriate feeding strategies to obtain maximum fish production from farm ponds at low/minimum investment costs was carried out under the Tamil Nadu-Irrigated Agriculture Modernization Project financed by the World Bank. The study was carried out for 180 days at the Directorate of Sustainable Aquaculture, Thanjavur, in four, equal-sized, farm ponds with two treatments in duplicates by stocking 5 species (Catla catla, Labeo rohita, Cirrhinus mrigala, Ctenopharyngodon idella and Cyprinus carpio) in the ratio of 1:1:1:1:2. Treatment 1 (T1) involved the feeding strategy of pelleted feed with 20% CP (crude protein) broadcast twice a day whereas in Treatment 2 (T2), the same feed was provided four times a day as feed balls using feed trays. Among the five species, C. carpio (779±189.01 g) and C. mrigala (670±121.38 g) stocked in T2 attained the maximum weight. Production parameters such as gross production, net production, average daily growth rate were not significant between the treatments, however T2 showed comparatively better results than T1. Survival rate of fishes was recorded significantly higher in T1 (35.54±2.60%) than in T2 (29.6±2.36%). Nutrients such as total phosphorus, total nitrogen and total potassium were significant and highly discharged in T1 than in T2. Experiment revealed that feeding fishes in trays helped to monitor the weight gain and feed intake with reduced nutrient discharge, thereby proper feed management was obtained in T2 when compared to T1